2011
DOI: 10.1091/mbc.e11-03-0271
|View full text |Cite
|
Sign up to set email alerts
|

The CSC is required for complete radial spoke assembly and wild-type ciliary motility

Abstract: Structural and functional analyses of artificial micro RNA (amiRNA) mutants reveal that the CSC plays a role not only in generating wild-type motility, but also in assembly of at least a subset of radial spokes. This study also produced the unexpected finding that, contrary to current belief, the radial spokes may not be homogeneous.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
115
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(127 citation statements)
references
References 43 publications
12
115
0
Order By: Relevance
“…Instead, they were identified in the pull-down of the anticalmodulin antibody. Knockdown of CSC proteins impaired RS2, RS3S, N-DRC, and a single-headed dynein, e (Dymek et al 2011;Heuser et al 2012), suggesting that the CSC is among the base of RS2 and RS3, N-DRC, and the nearby dynein. Consistent with this, the antibody for a CSC protein inhibits microtubule sliding velocity as the reduced microtubule sliding velocity of pf14 axonemes.…”
Section: Rs Outer Doublet Connectionsmentioning
confidence: 99%
“…Instead, they were identified in the pull-down of the anticalmodulin antibody. Knockdown of CSC proteins impaired RS2, RS3S, N-DRC, and a single-headed dynein, e (Dymek et al 2011;Heuser et al 2012), suggesting that the CSC is among the base of RS2 and RS3, N-DRC, and the nearby dynein. Consistent with this, the antibody for a CSC protein inhibits microtubule sliding velocity as the reduced microtubule sliding velocity of pf14 axonemes.…”
Section: Rs Outer Doublet Connectionsmentioning
confidence: 99%
“…The analysis of Chlamydomonas mutants has also revealed conserved axonemal components that transmit signals from the central pair and radial spoke structures to the dynein motors. Most notable are the calmodulin and spoke associated complex (CSC; Dymek et al 2011, Heuser et al 2012a) and the DRC; see the next section for insights from recent cryoelectron tomography (cryo-ET) analyses of the axoneme (for reviews, see Heuser et al 2009, Porter 2012) and of the Mia-I1 dynein complex (Yamamoto et al 2013). The CSC and the DRC play roles in the control of the dynein motors: They are both ideally located to link the radial spokes to the outer doublets and the dynein motors.…”
Section: And Lindemann and Lesich (2010)mentioning
confidence: 99%
“…The notable features in figure 4 include a definition of the longitudinal 96-nm axonemal repeat (figure 4 D and E), which is probably the basic unit of activity along the axoneme and the substructure of the outer dynein arms, including the resolution of the globular motor domains ( figure 4d-4g). Also illustrated are the locations and substructure of each inner dynein arm (I1/f dynein and dyneins a-g; Bui et al 2012, Heuser et al 2012b, Lin et al 2014, the N-DRC (Heuser et al 2009), the CSC (Dymek et al 2011, Heuser et al 2012a, and the radial spokes (Pigino et al 2011, Barber et al 2012, Oda et al 2014). In addition, cryo-ET has revealed the substructure of the central pair apparatus (Carbajal-Gonzalez et al 2013, Oda et al 2014).…”
Section: And Lindemann and Lesich (2010)mentioning
confidence: 99%
“…We typically use two to three constructs for each gene of interest. The frequency of knockdown ranges from 0 per 2000 to 1 per 38 transformants (DiPetrillo and Smith, 2010;Dymek et al, 2011) and four other genes (unpublished data). The source of this variability is unknown.…”
Section: Amirna Transformation and Screeningmentioning
confidence: 98%
“…We have tried numerous RNAi methods for reducing protein expression (unpublished results), and all of these methods produced a significant number of off-target effects. We have found that the amiRNA approach of Molnar et al (Molnar et al, 2009) generates strains with stable knockdown of protein expression without these off-target effects (reviewed in DiPetrillo and Smith, 2010;Dymek et al, 2011; and unpublished observations for three additional axonemal proteins). It is also possible the antibody used by Rasi and colleagues (Rasi et al, 2009) for screening knockdown of expression is not specific (supplementary material Fig.…”
Section: Rasi Et Al Recently Reported That Katanin Function Is Essenmentioning
confidence: 99%